Mrs. Gutierrez: Twelve Years After Bariatric Surgery - Carla Lupi; Anthony Oliva; Ansley Splinter (Association of American Medical Colleges, 2014)
Abstract Introduction This interdisciplinary problem-based learning case for third-year and advanced second-year students describes a woman urgently referred from her primary care provider to a neurologist several years after bariatric surgery. Learners will move through the unfolding diagnostic reasoning of a rare condition that presents identically to a common one, considering the importance of monitoring response to therapy as a means of confirming the original diagnosis, and the use of non-response to therapy as a trigger for reevaluation of that diagnosis. Methods This case provides the opportunity for students to "take the history" from the facilitator rather than simply receive predetermined information. It also invites students to review emerging guidelines on the long-term care of this growing population of patients, consider occupational exposures, and the use of the history to determine the likelihood of heavy menses as the cause of anemia in a woman. Advanced learners may also consider issues of cost-effectiveness of the diagnostic work-up, the communication challenge of explaining highly uncertain prognosis, ethical issues in the ongoing care of patients who lose insurance coverage, and best practices for the education and follow-up of these patients. Results We have formally surveyed 39 third-year students immediately after the session. All 39 students agreed or strongly agreed that this case improved their understanding of basic science concepts related to nutrition. Thirty-seven students agreed or strongly agreed that this case improved their understanding of the effects of different types of bariatric surgery on nutritional needs. All 39 students agreed or strongly agreed that the case was believable. Discussion We have used this case with students on the neurology clerkship at our institution for a cross-clerkship curriculum designed to help students integrate basic science into their rapidly-expanding clinical learning. Other curricular needs prompting us to write this case were in the areas of nutrition, reflection on diagnostic reasoning, and the care of the rapidly growing postbariatric surgery population.